Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Berdasarkan Kompetensi Pada Perum Bulog Divisi Regional Jawa Timur - Nirmala, Ariesta Fuji; Setyawan, Henry Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Agency Division Logistics which located in East Java is a public company of government which has basic value that are mobilize all units, concentrate employees’ performance and total of integrity to achieve the vision and mission of company. The units of human resource and law are responsible for coordinating the employees to do the best performance for company by executing the evaluation process of employee performance. Based on the observation and interview, the units of human resource and law have some problems during the process of evaluation of employees’ performance that are less effective and efficiency the procedure of performance so that there are delay of report and less exact of data. Based on two problems, there is an application solution for assessment of employee performance based on their competence. There are some capabilities of the application that are processing of data, calculating the results of assessment, determining the reward based on assessment of employee performance. The concept of the application is competence relation cause and effect so that we would know the competence of employees to determine the reward in the form of a promotion. Expectation of the application is overcome the problem occurred which compatible with user need and it is based on the test of performance assessment which compatible with employees’ competence to obtain the reward.